2019
DOI: 10.1111/joor.12922
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of erosive tooth wear in Chilean adults, 2016: A cross‐sectional study

Abstract: Objectives To determine the prevalence, severity and distribution of erosive tooth wear lesions in adult patients at the Universidad de los Andes Health Center in the San Bernardo Metropolitan Region, Chile, during a period of 4 months in 2016. Methods A cross‐sectional study was conducted. A consecutive sample of patients from 18 to 46 years old who were receiving care at the Universidad de los Andes Health Center during a period from September 2016 to January 2017 was analysed. Basic erosive wear examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
1
20
1
4
Order By: Relevance
“…A prevalência da erosão dentária está aumentando e torna-se uma preocupação para cirurgiões-dentistas, sendo um dos principais problemas de saúde bucal em crianças, adolescentes, jovens e adultos (Marró et al, 2019;Racki et al, 2020).…”
Section: Diagnósticounclassified
See 1 more Smart Citation
“…A prevalência da erosão dentária está aumentando e torna-se uma preocupação para cirurgiões-dentistas, sendo um dos principais problemas de saúde bucal em crianças, adolescentes, jovens e adultos (Marró et al, 2019;Racki et al, 2020).…”
Section: Diagnósticounclassified
“…A erosão dentária tem se destacado nos últimos anos, principalmente pela alta e crescente prevalência (Murakami et al, 2016), transformando-a um dos principais problemas de saúde bucal na infância, juventude e fase adulta (Marró et al, 2019;Racki et al, 2020).…”
Section: Introductionunclassified
“…Based on a sample size calculation with the following criteria, there was a 5% margin of error, a 0.05 alpha level, and a 75% expected tooth wear prevalence. [9][10][11][12] An estimated 323 participants were needed for this study (http://www. stat.ubc.ca/~rollin/stats/ssize/b1.html).…”
Section: Study Samplementioning
confidence: 99%
“…[6][7][8] Several global studies evaluated the prevalence and degree of tooth wear, which shed light on potential risk factors, such as sociodemographic factors and hygienic habits that contribute to the progression of the condition. [9][10][11][12] In Chengdu city, China, a study about the prevalence of tooth wear in adults showed that 63% suffered from tooth wear: age and intensity of toothbrushing were among the risk factors related to tooth wear. 9 Tooth wear of 97.9% was found in a study conducted in Chile, mainly affecting the anterior teeth, with no differences found between males and females; however, a positive correlation with age was observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation